Analisis Produktivitas Kerja Pegawai Pada Dinas Pendapatan Daerah Provinsi Sumatera Selatan - Jailani Jailani; Taufik Akhyar (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
This study aims to identify and describe the work productivity generated by the Regional Revenue Office Employees of South Sumatera Province by using qualitative descriptive approach method. This study uses instruments consisting of interviews with informants’ research, observation and literature. The data used in this study consist of qualitative data and quantitative data that derived from primary data and secondary data. The data were analyzed through the following stages: sorting, analysis/discussion, and conclusion. From the research, it is concluded that employee productivity seen from the aspect of efficacy is classified good because it has met the criteria of a productive employees. Employee productivity seen from the aspect of effectiveness is classified not good as there are still weaknesses on employee's ability to carry out the work procedures, where the work procedures carried out often don’t fit with the time to be completed. Seen from the employees’ ability in prioritizing work, it is known that there are still programs and activities that have not reached the target realization. There are still activities that cannot be carried out optimally by employees. Ability to cooperate possessed by the employees with other agencies in order to collect and manage regional revenue is classified not optimal yet. Employee productivity seen from the quickness response to work is classified not good enough because of the weakness of frequent employees out of the office during working hours. Keywords: Productivity, Employment, Employee